Hypertensive Disorders in Pregnancy (HDP): Diagnostics and Therapy. Guideline of the DGGG, OEGGG and SGGG (S2k-Level, AWMF Registry No. 015/018, June 2024) - Pecks, Ulrich; Baumann, Marc; Binder, Julia; Contini, Christine; Dathan-Stumpf, Anne; Dechend, Ralf; Enna-Kirchmair, Birgit; Fischer, Thorsten; Girard, Thierry; Greve, Susanne; Groten, Tanja; Hartung, Andreas; Kehl, Sven; Koch, Maria; Köbke, Andrea; Kranke, Peter; Lapaire, Olav; Mader, Silke; Rump, Lars Christian; Sperling, Alexandra; Stepan, Holger; Stracke, Sylvia; Verlohren, Stefan; von Versen-Höynck, Frauke; Winkler, Karl; Zemlin, Michael; Schlembach, Dietmar (Geburtshilfe und Frauenheilkunde, 2025)
Aim This S2k guideline of the German Society of Gynecology and Obstetrics (DGGG) contains consensus-based recommendations for the care and treatment of women with hypertension in pregnancy. It aims to serve as a guide for all professions involved in the care of pregnant women and to improve interprofessional and interdisciplinary cooperation. A new focus was placed on patientsʼ long-term health beyond the postpartum period.Methods The existing S2k guideline was revised and the relevant literature reviewed. Where new questions arose, they were formulated and developed in PICO format. A targeted systematic literature search was carried out using PubMed. Other international guidelines were also consulted. After summarizing and presenting the available data, recommendations and statements were developed, discussed, and agreed on by the guideline group.Recommendations The recommendations cover prediction, prevention, diagnosis, and treatment from the moment hypertensive disease is detected in pregnancy as well as postpartum, in the puerperium, and during breastfeeding. A major change from the previous version of the guideline is the reduction in blood pressure levels that should be achieved during pregnancy. Suggestions are made on how to proceed with regards to the long-term health of mother and child, which the guideline group believes is currently regulated inadequately in the German healthcare system.Ziel Diese S2k-Leitlinie der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG) enthält konsensbasierte Empfehlungen zur Betreuung und Behandlung von Frauen mit Hypertonie in der Schwangerschaft. Sie dient allen in der Betreuung schwangerer Frauen beteiligten Professionen als Orientierung und soll so die interprofessionelle und interdisziplinäre Zusammenarbeit verbessern. Ein Schwerpunkt wurde dabei neu auf die Langzeitgesundheit über das Wochenbett hinaus gelegt.Methoden Es wurde die bestehende S2k-Leitlinie überarbeitet und die entsprechende Literatur gesichtet. Wo sich neue Fragestellungen ergaben, wurden diese im PICO-Format formuliert und ausgearbeitet. Eine gezielte systematische Literaturrecherche mit Pubmed wurde durchgeführt. Ergänzend wurde auf andere internationale Leitlinien zurückgegriffen. Nach Zusammenfassung und Darstellung der zur Verfügung stehenden Daten wurden Empfehlungen und Statements in der Leitliniengruppe herausgearbeitet, diskutiert und abgestimmt.Empfehlungen Empfehlungen umfassen unter anderem die Prädiktion, Prävention, Diagnose und das Management bei Feststellung hypertensiver Erkrankungen in der Schwangerschaft und über die Geburt hinaus in Wochenbett und Stillzeit. Eine wesentliche Änderung im Vergleich zur Vorgängerversion der Leitlinie besteht in der Senkung der in der Schwangerschaft zu erzielenden Blutdruckwerte. Es werden Vorschläge für das Vorgehen in Bezug auf die Langzeitgesundheit von Mutter und Kind getätigt, die im deutschen Gesundheitswesen aktuell in den Augen der Leitliniengruppe ungenügend geregelt ist.
Keywords: guideline; pregnancy; hypertension; preeclampsia; screening; management; long-term health